Narratives at Play in Aeschylus: Perspectives on Genre and Poetics - Gianvittorio-Ungar, Laura (Brill, 2025)
The strong presence of embedded narratives in Aeschylus is often explained as a sign of the immaturity of the tragic genre in his time. Narratives at Play in Aeschylus analyses narrative features which were ostensibly constitutive of the genre for Aeschylus but later became more peripheral. The book reconstructs how these developments in tragedy affected the reception of Aeschylus, and tests new reading strategies that adapt readers' expectations to his texts. Die starke Präsenz eingebetteter Erzählungen bei Aischylos wird oft als Zeichen für die Unreife der tragischen Gattung zu seiner Zeit erklärt. Narratives at Play in Aeschylus analysiert textnah narrative Merkmale, die für Aischylos offenbar gattungskonstituierend waren und später peripherer wurden. Das Buch rekonstruiert, wie diese tragischen Entwicklungen die Rezeption des Aischylos beeinträchtigten, und testet neue Lesestrategien, die die Erwartungen der Leser an seine Texte anpassen.